REALISASI PENANGANAN PERUBAHAN IKLIM DI INDONESIA MELALUI IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGs): TUJUAN-13.1.3 - Idrus, Muh. Rizky Hikmatullah; Usi, Usi Alfiani Nur (Indonesian Association for International Relations, 2024)
This article aims to know the realization of handling climate change in Indonesia through the implementation of Sustainable Development Goals (SDGs): Goals-13.1.3 which focuses on implementing regional disaster management strategies in Indonesia in the 2017-2019 period. The method used in this research is a qualitative method and a literature review of various literature discussing handling climate change in Indonesia. The green theory perspective is used in analyzing the realization of Goals-13.1.3 in Indonesia. The research results show that the realization of handling climate change through the implementation of SDGs Goals-13.1.3 falls into the category of anthropocentric understanding and shallow environmental understanding; as well as placing greater emphasis on environmental sustainability by aligning people's consumption levels without excessive consumption; Regular environmental preservation and implementation of regional disaster management strategies will shape sustainable development in Indonesia